WASIAT WAJIBAH DAN PERKEMBANGANNYA - Nofiardi, Nofiardi (Alhurriyah, 2009)
The presence of dying exhortation in Islamic law takes part in an important rule to avoid the turbulences inside of a family. As we know, that sometimes a family member could not receive the wealth left by inheritance way. However, he or she has taken apart for supplying the inheritance wealth. By the existence of inheritance wealth (the obligated dying exhortation) arranged in Islam, the disappointments could be overcome.